Collectivist culture, environmental regulation and pollution emissions: evidence from China - Zhang, Li; Zhang, Miao; Jia, Jie; Peng, Xu; Zhu, Jiaxuan; You, Shibing (Frontiers in Psychology, 2024)
Collectivist culture serves as a significant cultural foundation in China. It could, to some extent, shape public attitudes towards the environment and thus influence the implementation of related policies. To examine this hypothesis, this study constructs the collectivist culture intensity index for 25 Chinese provinces spanning from 2010 to 2020. Through a fixed-effect model, we explore how the collectivist culture intensity affects pollution emissions in China. The empirical results indicate the significance of collectivism in enhancing emission reduction through environmental regulations. This conclusion remains robust even when excluding the impact of endogeneity concerns by adopting the instrumental variable approach. Heterogeneity analysis shows that collectivism is more effective in enhancing market-based environmental regulations rather than those driven by policies. Further mechanism analysis confirms that green innovation is a crucial pathway through which collectivism influences pollution emissions. These findings here will offer guidance to policymakers when formulating environmental policies for contexts with different regional cultures.